Advanced and refractory ceramics for energy conservation and efficiency : a collection of papers presented at CMCEE-11, June 14-19, 2015, Vancouver, BC, Canada /: a collection of papers presented at CMCEE-11, June 14-19, 2015, Vancouver, BC, Canada. ([2016]) - Unknown
No abstract available